Índice de salubridade ambiental para comunidades rurais da Amazônia: estudo de caso da Comunidade Nova Canaã em Manaus/AM - Rodrigues, Alice Flávia Bezerra (Brasil, 2024)
This research presents the formula for the Rural Environmental Health Index (ISARural) as a tool for assessing environmental health and sanitation conditions in a rural community in the Amazon, Nova Canaã. The index was constructed in four stages: a systematic literature review of online databases; selection of indicators and variables that are similar to the community under study in order to develop the index; definition of scoring criteria, development of a survey and choice of method for formulating the index; and an on-site visit to apply the survey, take photographs and collect and analyze the data. Based on the methodology applied, the ISARural for the Nova Canaã Community had a score of 63.93, classified as Medium Health. Among the partial indices that compose the ISARural, the one that most positively influenced the result was Water Supply and the one that most negatively influenced it was Domestic Sanitary Sewage. These results are mostly due to the incorrect disposal of wastewater and the poor condition of road surfaces and rainwater drainage, three related partial indices that have a direct impact on the health conditions of the local population, and which could have their negative implications minimized by public authorities.